Effect of 17% ethylenediaminetetraacetic acid and silver citrate on sealer resin penetration in the apical third - Kurmaena, Iceu Estu; Nurliza, Cut; Gani, Basri A. (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Endodontic sealers limit bacteria growth and clean the smear layer of the root canal. Biocompatible irrigants silver citrate and ethylenediaminetetraacetic acid (EDTA) have a chelating agent that increases sealer penetration in dentinal tubules. Purpose: This study aims to investigate the final irrigation difference in epoxy resin and bioceramic sealer penetration into dentinal tubules at the apical third. Methods: A total of 30 extracted mandibular premolars were split into six groups; three received epoxy resin sealer and three received bioceramic resin with aquadest, silver citrate (BioAKT) or EDTA 17% irrigation. A confocal laser scanning microscope estimated sealer penetration in dentinal tubules. For quantitative data analysis, Olympus Fluoview ver.4.2a was used. Results: Silver citrate final irrigation with bioceramic resin sealer had the highest dentinal tubular penetration (24%; 1,431 µm), followed by EDTA 17% (20%; 1,202 µm), aquadest (16.3%; 969 µm), EDTA 17% with epoxy resin (15.8%; 938 µm, 14%; 803 µm), and distilled water (10%; 584 µm). Significant differences existed in all groups (p = 0.001). Epoxy resin sealer penetration into dentinal tubules was similar between final irrigants (p = 0.257) and bioceramic resin groups (p = 0.658). Conclusion: Silver citrate (BioAKT), a bioceramic resin sealer-based final irrigation solution, penetrates dentinal tubules better for endodontic therapy.